5x+7-2(x+5)=x-10+2(x-3)

Simple and best practice solution for 5x+7-2(x+5)=x-10+2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7-2(x+5)=x-10+2(x-3) equation:



5x+7-2(x+5)=x-10+2(x-3)
We move all terms to the left:
5x+7-2(x+5)-(x-10+2(x-3))=0
We multiply parentheses
5x-2x-(x-10+2(x-3))-10+7=0
We calculate terms in parentheses: -(x-10+2(x-3)), so:
x-10+2(x-3)
determiningTheFunctionDomain x+2(x-3)-10
We multiply parentheses
x+2x-6-10
We add all the numbers together, and all the variables
3x-16
Back to the equation:
-(3x-16)
We add all the numbers together, and all the variables
3x-(3x-16)-3=0
We get rid of parentheses
3x-3x+16-3=0
We add all the numbers together, and all the variables
13!=0
There is no solution for this equation

See similar equations:

| x²+2x-24=0 | | 23-4r=11 | | 25x+12=10-8 | | 13(c+1)=13 | | h–1.8=3.2 | | -16s+-8s+-15=9 | | -(6x/5)+5=35 | | q/3-1=3 | | 6x+20=8x+90 | | -a/5-12=10 | | 5-(2x+4)=13 | | 12+v=8 | | 15k+-17k=-20 | | 250(0.25)+0.2x=(250+x)(0.3) | | 4j+-5j=6 | | 5.{2x+4}=30 | | 2x+3/10+4x-1/10=3/10 | | 6a-7+2=—23 | | 2x+3(x-1)=4x+6 | | -2x+13+3x=2+x+11 | | 2{x+1}=12 | | 4=4y-12 | | 3(x+7)=2x+4322 | | 2/3x=x-15 | | y/4+4=-15 | | 2{x+1=12 | | 2(-5+8z)=-5+8z | | x/1.5=16= | | 8=x-3/7 | | 8-9(-2x-1)=3+6x | | v/4+15=18 | | 35=1/2b(7) |

Equations solver categories